Envisioning science: Marie Curie’s journey from Poland to Paris - Odlin, Sue; Fleming, Jean (New Zealand Science Review, 2011)
​All my mind was centred on my studies. I divided my time between courses, experimental work, and study in the library. In the evening I worked in my room, sometimes very late into the night. All that I saw and learned was a new delight for me. It was like a new world open to me, the world of science which I was at last permitted to know in all liberty. (Marie Curie cited by Goldsmith 2004, p. 49)